Determinant of Students’ Academic Triumph via Class Attendance - Amos Ochayi Onojah; Adenike Aderogba Onojah; Christianah Oluwakemi Aransiola (RIRAI Publisher, 2020)
The study investigated the influence of students’ attendance for lecture on their academic performance and the interactive effect of students’ IQ on students’ academic achievement. The study adopted a true experimental treatment design. 30 computer science students and 50 educational technology students were purposively sampled. Four educational technology lecturers from the department of educational technology, University of Ilorin validated the lesson plan and the performance test that covered the content on a selected Educational Technology concept. Mean and percentage were used to answer the research questions. For hypothesis testing, pearson product moment correlation (PPMC) was used to test hypothesis one while Hypothesis two was analyzed using ANCOVA. All hypotheses were tested at 0.05 level of significance. The findings established that there was significant influence of class attendance on their academic performance but there was no significant interactive effect of students’ IQ on students’ academic achievement. The study concluded that students who attended class regularly perform better than those who do not.